(untitled) (Journal of the Bangladesh Agricultural University, 2012)
The main purpose of the study was to produce esterified solid fat (ESF) from fractionated rapeseed oil and palm stearin through lipase-catalyzed reaction. The response surface methodology (RSM) was applied for optimization of three reaction factors such as substrate mole ratio, enzyme percent, and reaction time. The design was adequate and reproducible due to satisfactory levels of coefficient of determination (R2, 0.98) for both cases and coefficient variation (CV, 4.06 for SFC at 10 °C and 7.95 for SFC at 30 °C, respectively). The substrate mole ratio was the significant term for affecting the response of SFC (P<0.05) rather than reaction time and enzyme percent. Based on ridge analysis, the production of ESF with SFC 51.48 ±0.94 % at 10 ºC would be predicted by the combinations of optimized 24.07 h reaction time, 10.66 % enzyme and 1: 1.52 substrate mole ratios. On the other hand, the SFC of 21.44±0.83 at 30 ºC would be predicted by the combinations of optimized 24.37 h reaction time, 10.23 % enzyme and 1: 1.5 substrate mole ratios. The ESF contained mainly of palmitic (45.1%), oleic (40.8%), linoleic (5.6%) and stearic (4.5%) acids, respectively. The total sterol and tocopherol contents of ESF were 243.27 mg/100g and 19.26 mg/100 g, respectively. Therefore, these results in this study suggested that RSM can be used to optimize the lipase-catalyzed synthesis of ESF with suitable physical characteristics. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11040 J. Bangladesh Agril. Univ. 9(2): 273282, 2011